SNAKE LINE ANALYSIS FOR LAHAR FLOW WARNING SYSTEM (CASE STUDY IN PUTIH RIVER, MOUNT MERAPI) - Nina Yulinsa (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2015)
Lahar flow in the region of Mount Merapi after an eruption of 2010 is still considered potentially to happen and threat the region along the river from the upstream. The development of warning criteria against the potential occurrence of lahar flow is a thing that should be done continuously to accommodate dynamics data availability (rainfall data and lahar flow occurrence data), although with limited data. This study aims to develop lahar warning system applying snake line as a rain phenomenon in Putih catchment area which will affect the occurrence of lahar flow and to evaluate the success rate of snake line for deciding the warning system. This study used the main reference from Guidelines for Development of Warning and Evacuation System against Sediment Disasters in Developing Countries released by Ministry of Land, Infrastructure and Transport Infrastructure Development Institute – Japan (2004). This research was conducted through several stages, i.e. secondary data collection in the form of rainfall data, lahar flow occurrence data, making correlation graph between rainfall intensity and working rainfall, determination of critical line, warning line and evacuation line. The results show that standard rainfall for warning and evacuation alert in Putih River are 22 mm, and 49 mm, respectively. The accuracy of warning criteria and the evacuation criteria against snake line for warning line is 30%, evacuation line is 61% and the critical line is 83%. The behavior of snake line that indicates lahar flow occurrence in Putih River forming an angle of 40o up to 45o.